(untitled) (Web of Teachers: Inderscience Research, 2025)
The article examines the scientific and methodological foundations for integrating web-quest technology into language and cultural education. The relevance of the study is determined by globalization, digital transformation, and the expansion of distance and blended learning formats, which require innovative pedagogical solutions. Based on systemic, communicative-activity, and sociocultural approaches, the didactic potential of web-quests is analyzed, and principles for their design and implementation are identified. An integrative model of web-quest application aimed at developing foreign language communicative and intercultural competence among philology students is substantiated. The study demonstrates that the use of authentic online resources and problem-based tasks enhances learner motivation, autonomy, and critical thinking.